UNDERSTANDING ONLINE PURCHASE INTENTION IN E-COMMERCE: THE MEDIATING ROLE OF CUSTOMER ENGAGEMENT BETWEEN OMNICHANNEL INTEGRATION AND INFLUENCER CREDIBILITY - Deandra Vidyanata; Ni Putu Dyah Krismawintari; Rifka Utami Arofah; Lenny Dermawan Sembiring (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
The rapid development of e-commerce and omnichannel strategies have changed digital consumer behavior significantly, but studies regarding the integration of digital channels and influencer credibility in shaping online purchase intentions still show conceptual inconsistencies, especially regarding the psychological mechanisms that bridge this relationship. This research aims to analyze the influence of omnichannel integration and influencer credibility on online purchase intention by placing customer engagement as a mediating variable. The research uses a quantitative approach through an online survey of 250 e-commerce users in Indonesia who were selected using a purposive sampling technique. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test direct and indirect relationships between variables. The research results show that omnichannel integration and influencer credibility have a positive and significant effect on customer engagement, which in turn increases online purchase intention substantially. Apart from that, customer engagement is proven to partially mediate the relationship between omnichannel integration and influencer credibility on online purchase intention. These findings strengthen the engagement-based consumer behavior perspective by integrating technological dimensions and social influence in the context of modern e-commerce. Practically, this research provides strategic implications for e-commerce players to optimize cross-channel integration and utilize credible influencers to increase customer engagement.